A novel chemotherapy strategy for advanced hepatocellular carcinoma: a multicenter retrospective study. Issue 19 (5th October 2022) - Sun, Juxian; Liu, Chang; Shi, Jie; Wang, Nanya; Jiang, Dafeng; Mao, Feifei; Gu, Jingwen; Zhou, Liping; Shen, Li; Lau, Wan Yee; Cheng, Shuqun
Abstract: Background: Chemotherapy is a common treatment for advanced hepatocellular carcinoma, but the effect is not satisfactory. The study aimed to retrospectively evaluate the effects of adding all-trans-retinoic acid (ATRA) to infusional fluorouracil, leucovorin, and oxaliplatin (FOLFOX4) for advanced hepatocellular carcinoma (HCC). Methods: We extracted the data of patients with advanced HCC who underwent systemic chemotherapy using FOLFOX4 or ATRA plus FOLFOX4 at the Eastern Hepatobiliary Surgery Hospital, First Hospital of Jilin University, and Zhejiang Sian International Hospital and retrospectively compared for overall survival. The Cox proportional hazards model was used to calculate the hazard ratios for overall survival and disease progression after controlling for age, sex, and disease stage. Results: From July 2013 to July 2018, 111 patients with HCC were included in this study. The median survival duration was 14.8 months in the ATRA plus FOLFOX4 group and 8.2 months in the FOLFOX4 only group ( P  < 0.001). The ATRA plus FOLFOX4 group had a significantly longer median time to progression compared with the FOLFOX4 group (3.6 months vs. 1.8 months, P  < 0.001). Hazard ratios for overall survival and disease progression were 0.465 (95% confidence interval: 0.298–0.726; P  = 0.001) and 0.474 (0.314–0.717; P  < 0.001) after adjusting for potential confounders, respectively. Conclusion: ATRA plus FOLFOX4 significantly improves the overall survival and time to disease progression in patients with advanced HCC.